The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1002/star.19860380206
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Properties of Starch in Cassava Varieties in Relation to Age of the Crop

Abstract: Cassava starch extracted from six varieties at different period of growth was examined for various physiochemical properties. The granule size increased in all the six varieties upto 6th month from time of tuber initiation and thereafter remained almost constant. The amylose content and reducing values did not vary much at different stages of growth. The swelling volume and swelling power of starch showed large variations particularly after 10th month. Such changes of four varieties were not noticed in other v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
3
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 7 publications
(1 reference statement)
4
71
3
3
Order By: Relevance
“…Moorthy and Ramanujam (1986) reported that the swelling power of flour granules is an indication of the extent of associative forces within the granule. Therefore, the higher the swelling power, the higher the associate forces.…”
Section: Resultsmentioning
confidence: 99%
“…Moorthy and Ramanujam (1986) reported that the swelling power of flour granules is an indication of the extent of associative forces within the granule. Therefore, the higher the swelling power, the higher the associate forces.…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences (p < 0.05) existed in the swelling power of the cassava flour samples. Moorthy and Ramanujam [16] reported that swelling power of cassava flour is dependent on the variety, environmental factors and the age of the crop. Aryee et al [8] also reported that the swelling power of the flour samples of cassava varieties to be 5.87% to 13.48%.…”
Section: Swelling Power Of Cassava Varietiesmentioning
confidence: 99%
“…Broni bankye had the lowest (73.04%), with Bankye fitaa having the highest (79.98%). Solubility is dependent on variety, environmental factors and age of the crop [16]. Aryee et al [8] also reported that low swelling accompanied by the high solubility is indicative of the weak associative forces in the starch granules in these varieties.…”
Section: Solubility Of Cassava Varietiesmentioning
confidence: 99%
See 2 more Smart Citations